2020
DOI: 10.1186/s12935-020-01672-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing immune infiltration and the tumor microenvironment for the diagnosis and prognosis of sarcoma

Abstract: Background Sarcomas, cancers originating from mesenchymal cells, are comprehensive tumors with poor prognoses, yet their tumorigenic mechanisms are largely unknown. In this study, we characterize infiltrating immune cells and analyze immune scores to identify the molecular mechanism of immunologic response to sarcomas. Method The “CIBERSORT” algorithm was used to calculate the amount of L22 immune cell infiltration in sarcomas. Then, the “ESTIMATE”… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 69 publications
(73 reference statements)
4
27
0
Order By: Relevance
“…Therefore, the activation of NK cells is significantly correlated with better prognosis, while the higher levels of resting NK cells infiltration indicate a worse chance of survival in human malignancies ( Bigley and Simpson, 2015 ; Bisheshar et al, 2020 ). Similarly, the infiltration of M0 macrophages is positively related to poor clinical outcomes in human malignancies, including STS, which aligns with the findings of our study ( Zhu and Hou, 2020 ). Thus, the worse clinical outcomes of the high-risk group may be associated with infiltrating immune cellular populations, and m6A-regulated lncRNAs may function as critical modulators of immune cell infiltration in STS.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the activation of NK cells is significantly correlated with better prognosis, while the higher levels of resting NK cells infiltration indicate a worse chance of survival in human malignancies ( Bigley and Simpson, 2015 ; Bisheshar et al, 2020 ). Similarly, the infiltration of M0 macrophages is positively related to poor clinical outcomes in human malignancies, including STS, which aligns with the findings of our study ( Zhu and Hou, 2020 ). Thus, the worse clinical outcomes of the high-risk group may be associated with infiltrating immune cellular populations, and m6A-regulated lncRNAs may function as critical modulators of immune cell infiltration in STS.…”
Section: Discussionsupporting
confidence: 92%
“…While the enrichment of unpolarized M0 macrophages in the tumor microenvironment has been demonstrated to be detrimental for survival of patients with hepatocellular carcinoma and sarcoma 16,40 , their role in MDS and other hematologic malignancies has been scarcely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Dhupkar et.al indicated that osteosarcoma lung metastases regression by anti-PD1 can be attributed to activated tumor macrophages M1 and reduced macrophages M2 [ 50 ]. Although there are few studies focused on macrophages M0, its relationship with other immune cells, such as CD8 T cells, has also been preliminarily reported [ 51 ]. Natural killer (NK) cells are important immune cells in the innate immune mechanisms.…”
Section: Discussionmentioning
confidence: 99%